MENYOAL PERTANGGUNGJAWABAN HUKUM PIDANA TERHADAP TINDAKAN MALAPRAKTIK KEDOKTERAN DI TENGAH PANDEMI COVID-19 DI INDONESIA - T. Subarsyah (Faculty of Law, Universitas Gadjah Mada, 2022)
Abstract Indications of malpractice by medical personnel when handling Covid-19 cases are in the public spotlight quite seriously. These actions are feared to be a bad image and a frightening specter for patients and the general public. This paper aims to answer the doctor's criminal responsibility due to negligence in handling the health of patients infected with Covid-19. The approach method is normative juridical by examining the legislation, and various legal literature that supports writing. The result of the study is a description of the doctor's responsibility due to negligence from the juridical aspect in the form of analytical descriptive. As for the conclusions, the impact of malpractice and the responsibility of doctors in terms of criminal, civil and code of ethics. AbstrakIndikasi adanya tindakan malapraktik oleh tenaga medis saat penanganan kasus Covid-19 menjadi sorotan publik yang cukup serius. Tindakan tersebut dikhawatirkan menjadi citra buruk dan momok menakutkan bagi pasien dan masyarakat umum. Tulisan ini bertujuan untuk menjawab pertanggung jawaban pidana dokter akibat kelalaian penanganan kesehatan pasien yang terinfeksi Covid-19. Metode pendekatan melalui yuridis normatif dengan menelaah peraturan perundang-undangan, dan berbagai literatur ilmu hukum yang mendukung tulisan. Hasil telaah berupa gambaran pertanggung jawaban dokter akibat kelalaian dari aspek yuridis dalam bentuk deskriptif analitis. Adapun kesimpulan, dampak malapraktik dan pertanggung jawaban dokter dari sisi pidana, perdata dan kode etik.